2001
DOI: 10.1002/ajmg.10110
|View full text |Cite
|
Sign up to set email alerts
|

All in the family: Evaluation of the process and content of sisters' communication about BRCA1 and BRCA2 genetic test results

Abstract: Despite the potential importance of family communication, little is known about the process and content of communicating BRCA1/2 test results to relatives. The objectives of this observational study were to describe the process and content of communicating BRCA1/2 test results to sisters, and to evaluate whether the proband's carrier status influenced communication outcomes. Participants were 43 women who were the first family member to have genetic testing (probands). Probands reported on communication outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
210
3
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 192 publications
(226 citation statements)
references
References 24 publications
11
210
3
2
Order By: Relevance
“…Evidence strongly suggests that reciprocal social support, compared to one-way provision or receipt of support, are especially important on the well-being of older adults (Heaney and Israel 2008;House et al 1988). Previous studies showed that social support exchanges among family members were associated with communication of disease risks within the family (Hughes et al 2002;Koehly et al 2009;van Oostrom et al 2007a). Thus, it is possible that the extent to which reciprocal social support exchange occurs within family systems determines older adults' desire and ability to share FHH information with family members.…”
Section: Sharing Family Health History (Fhh) Informationmentioning
confidence: 99%
“…Evidence strongly suggests that reciprocal social support, compared to one-way provision or receipt of support, are especially important on the well-being of older adults (Heaney and Israel 2008;House et al 1988). Previous studies showed that social support exchanges among family members were associated with communication of disease risks within the family (Hughes et al 2002;Koehly et al 2009;van Oostrom et al 2007a). Thus, it is possible that the extent to which reciprocal social support exchange occurs within family systems determines older adults' desire and ability to share FHH information with family members.…”
Section: Sharing Family Health History (Fhh) Informationmentioning
confidence: 99%
“…Some tellers were able to overcome their concerns and fulfill the duty they felt to inform their family members, often by clinging to the hope of scientific progress (Hallowell et al, 2003). Others felt that the potential for disturbing or upsetting their relatives outweighed the benefits of disclosing, at least for the time being (Hallowell, 1999;Bradbury et al, 2007;Hallowell et al, 2005a;Hughes et al, 2002).Other less commonly mentioned barriers or deterrents for disclosures to family members included geographic distance Green et al, 1997), the assumption other relatives would disclose the information to family members (Claes et al, 2003), dilemmas 16 between family members about how to best disclose to others (Hallowell et al, 2005a), the teller's lack of confidence in their own communication skills (Daly et al, 2001;, the fear that the information would be misunderstood by family members (Hughes et al, 2002;Hamilton et al, 2005) and thinking the information would not be useful to the family member (Forrest et al, 2003;MacDonald et al, 2007;Daly et al, 2001;Claes et al, 2003). …”
mentioning
confidence: 99%
“…Finally, this study might have overlooked other potential predictors of family relationship effects; family communication is probably one of them. Even if the genetic test result per se is known to be communicated to a great proportion of first-degree relatives, 15,16 less is known about the manner of telling, the information conveyed, and subsequent discussions about hereditary cancer. 1 Clearly, this important research area is embedded with several challenges, including the development of valid and sensitive measures of the unfolding process of family communication.…”
Section: Discussionmentioning
confidence: 99%
“…14 Previous studies have shown that individuals undergoing BRCA1/2 genetic testing share their test result with most, but not all, of their first-degree relatives quickly after it is disclosed. 15,16 Motivations to communicate include the desire to obtain social support and to offer advice about preventive health strategies. 15,17 Reasons for not communicating results to relatives include lack of a close relationship, infrequent communication, or thinking that the genetic information might upset a particular relative.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation